Navigating health challenges: the interplay between occupation-imposed movement restrictions, healthcare access, and community resilience - Oqab Jabali; Abed Alkarim Ayyoub; Shaden Jabali (BMC, 2024)
Abstract Background Transportation plays a significant role in health, community resilience, and access to basic needs such as healthcare, social services, education, and job opportunities. Health and community resilience are, however, impacted by a multitude of complex and unequal factors, such as transportation restrictions exacerbated by the Israeli occupation. The goal of the research was to examine the intricate relationships that exist in Palestine between movement restrictions imposed by occupation, health outcomes, and community resilience. Method A self-structured questionnaire, devised based on expert conversations and previous literature, was used in this descriptive, quantitative study to explore health and resilience outcomes. Age, gender, marital status, place of residence, and means of transportation were among the various factors that were utilized to describe the socio-demographics of the study sample (n = 202). The researchers employed stepwise multiple regression and descriptive statistics for the data analysis. Results Study findings indicated that transportation restrictions have significant direct and indirect health consequences. A significant direct effect is observed, signifying a negative correlation between restrictions and health; increased transportation restrictions are consistently correlated with a decline in health. The study emphasized how place of residence affects health outcomes, with higher scores for campers and people living in green line areas. It also underscores that public means of transportation are found to be better for health outcomes than private cars. Conclusion This study emphasized that roadblocks, checkpoints, and military incursions make it difficult for Palestinians to receive medical care, which has a detrimental impact on their health and well-being. It also underscores the need for significant reforms in Palestinian health and transportation systems to enhance infrastructure and healthcare access. The Palestinian Authority should invest in public transportation and community resilience programs to address transportation-related health issues, especially in villages, due to frequent settler attacks.